Cowboy Bebop, the movie - Watanabe, Shinichiro; Bones (Firm); Columbia TriStar Home Entertainment (Firm); Sunrise Illustration and Computer Animation; Bandai Bijuaru Kabushiki Gaisha (Culver City, CA: Columbia Tristar, 2003)
A terrorist bomb destroyed a tanker truck on Highway One on Mars releasing a deadly virus killing hundreds. The rewards for the bomber's capture is massive and the bounty hunter crew of the spaceship Bebop would love to get their hands on it.
Based on the story by Hajime Yatate.
Special features: The Making of Cowboy Bebop: 6 Behind-the -scene featurettes - Music videos for "Ask DNA" and "Gtta Knock a little harder" - Conceptual art galleries - Storyboard comparisons - ...Theatrical trailers - Animated menus.
Anime
Screenplay, Keiko Nobumoto ; character design and animation director, Toshihiro Kawamoto ; music, Yoko Kanno ; director of photography, Yoichi Ogami ; editor, Shuichi Kakesu
MPAA rating: R for some violent images.
DVD.
Keywords: Feature films -- Japan; Foreign films; Animation (Cinematography) -- Japan; Motion pictures, Japan; Science fiction films; Feature films; Animated films -- Japan; Films for the hearing impaired; Anime